People getting a grip on arthritis II: An innovative strategy to implement clinical practice guidelines for rheumatoid arthritis and osteoarthritis patients through Facebook. (January 2014) - Brosseau, Lucie; Wells, George A; Brooks, Sydney; De Angelis, G; Bell, Mary; Egan, Mary; Poitras, Stephane; King, Judy; Casimiro, Lynn; Loew, Laurianne; Novikov, Michael
Objective: The purpose of the study is to determine if an updated online evidence-based educational programme delivered through Facebook is effective in improving the knowledge, skills, and self-efficacy of patients with arthritis in relation to evidence-based self-management rehabilitation interventions for osteoarthritis (OA) and rheumatoid arthritis (RA). Methods: Adult patients (>18 years old) with self-reported OA or RA were eligible for the study. One-hundred-and-ten participants were recruited from the general public and different arthritis patient organizations throughout Canada. Eleven participants were selected to participate in focus groups to select effective self-management strategies for OA and RA according to level of implementation burden. Ninety-nine participants were then selected to participate in the online Facebook intervention which included a 'group' web page providing case-based video clips on how to apply the selected self-management interventions. Over a three-month period participants were asked to complete three online questionnaires regarding their previous knowledge, intention to use/actual use of the self-management strategies, self-efficacy and confidence in managing their condition. Results: Knowledge acquisition scores improved among OA and RA participants with a mean difference of 1.8 ( p < 0.01) when compared from baseline to immediate post-intervention. At three months post-intervention, almost all self-management strategies were successful with participants following through on their intention to use the self-management strategies; however, statistically significant results were only demonstrated for 'aquatic jogging' ( p < 0.05) and 'yoga' ( p < 0.05) among OA participants, and 'aquatic therapy' ( p < 0.01) among RA participants. Self-efficacy was maintained from immediate post-intervention to three months follow-up, and confidence improved as the study progressed. Conclusions: This online programme can provide patient organization representatives with the opportunity to learn about and integrate evidence-based self-management strategies for OA and RA in their daily lives, to increase their awareness of useful community resources, and support their efforts to disseminate the information to others with arthritis.